Kalender Zonal sebagai Upaya Unifikasi Awal Bulan Kamariah Gagasan Abdurrahman Özlem - Elly Uzlifah; Putri Firdiniah, Nur Eka (UIN ALAUDDIN MAKASSAR, 2024)
For Muslims, the need for a uniform calendar is urgent, because many Muslim worship activities are related to time. However, until now a single and universally applicable Lunar Calendar has not been realized. Currently, Muslims in the world still use the calendar that applies in their respective regions or countries. One of the researchers who is concerned with the zonal calendar problem is Abdurrahman Özlem. He was an amateur Muslim astronomer from Turkey who introduced the zonal calendar with the concept of the International Lunar Date Line. Apart from the concept initiated by Abdurrahman Özlem, there are actually several other zonal calendar concepts that have been initiated by other scientists. However, until now the Universal Lunar Calendar has not been realized. This paper examines Abdurrahman Özlem's ideas regarding a zonal calendar with the concept of lunar date boundaries with the visibility of the new moon. From the results of the study, it was found that the idea offered by Abdurrahman Özlem left problems regarding the time of tarawih and sahur prayers. Abdurrahman Özlem's calendar concept has not been able to solve the problem of differences in the Hijri calendar, but it has had an influence on the formation of criteria for visibility of the new moon and other lunar calendar models, namely the zonal calendar and the universal calendar as an effort to unify the lunar calendar.